Why expert leaders matter: a study on the mechanism of team value creation in knowledge-intensive teams - Zuomiao Xie; Yuanyuan Li; Shiqi Yuan; Jinjing Zhu (Humanities & Social Sciences Communications)
Abstract In the knowledge economy, expert-led teams emerge as a pivotal strategy for organizations to secure and maintain a competitive edge. Expert leaders have been shown to have a significant influence on team effectiveness in numerous knowledge-intensive teams. Using an evolutionary game model, this study explores the fundamental mechanism in the value creation process by experts-led teams and finds out: First, experts’ role modeling, coaching, and professional authority motivate team members to contribute their efforts and abilities, leading to the 1 + 1 > 2 synergistic effect. Second, among various forms of team value creation, expert-led teams are a crucial organizational structure which enables stable and long-term enhancements in accumulating team human capital to improve productivity. Moreover, the greater the role played by expert leaders, the faster the evolution progresses of team members’ abilities. This study emphasizes the importance of using expert leaders in human resource management to promote the effectiveness of knowledge-intensive teams.